MicroRNA changes of bone marrow-derived mesenchymal stem cells differentiated into neuronal-like cells by Schwann cell-conditioned medium - Wei, Zhi-Jian (Neural Regen Res, 2019)
Bone marrow-derived mesenchymal stem cells differentiate into neurons under the induction of Schwann cells. However, key microRNAs and related pathways for differentiation remain unclear. This study screened and identified differentially expressed microRNAs in bone marrow-derived mesenchymal stem cells induced by Schwann cell-conditioned medium, and explored targets and related pathways involved in their differentiation into neuronal-like cells. Primary bone marrow-derived mesenchymal stem cells were isolated from femoral and tibial bones, while primary Schwann cells were isolated from bilateral saphenous nerves. Bone marrow-derived mesenchymal stem cells were cultured in unconditioned (control group) and Schwann cell-conditioned medium (bone marrow-derived mesenchymal stem cell + Schwann cell group). Neuronal differentiation of bone marrow-derived mesenchymal stem cells induced by Schwann cell-conditioned medium was observed by time-lapse imaging. Upon induction, the morphology of bone marrow-derived mesenchymal stem cells changed into a neural shape with neurites. Results of quantitative reverse transcription-polymerase chain reaction revealed that nestin mRNA expression was upregulated from 1 to 3 days and downregulated from 3 to 7 days in the bone marrow-derived mesenchymal stem cell + Schwann cell group. Compared with the control group, microtubule-associated protein 2 mRNA expression gradually increased from 1 to 7 days in the bone marrow-derived mesenchymal stem cell + Schwann cell group. After 7 days of induction, microRNA analysis identified 83 significantly differentially expressed microRNAs between the two groups. Gene Ontology analysis indicated enrichment of microRNA target genes for neuronal projection development, regulation of axonogenesis, and positive regulation of cell proliferation. Kyoto Encyclopedia of Genes and Genomes pathway analysis demonstrated that Hippo, Wnt, transforming growth factor-beta, and Hedgehog signaling pathways were potentially associated with neural differentiation of bone marrow-derived mesenchymal stem cells. This study, which carried out successful microRNA analysis of neuronal-like cells differentiated from bone marrow-derived mesenchymal stem cells by Schwann cell induction, revealed key microRNAs and pathways involved in neural differentiation of bone marrow-derived mesenchymal stem cells. All protocols were approved by the Animal Ethics Committee of Institute of Radiation Medicine, Chinese Academy of Medical Sciences on March 12, 2017 (approval number: DWLI-20170311).